An enhanced pattern detection and segmentation of brain tumors in MRI images using deep learning technique - Kiran, Lubna; Zeb, Asim; Rehman, Qazi Nida Ur; Rahman, Taj; Shehzad Khan, Muhammad; Ahmad, Shafiq; Irfan, Muhammad; Naeem, Muhammad; Huda, Shamsul; Mahmoud, Haitham (Frontiers in Computational Neuroscience, 2024)
Neuroscience is a swiftly progressing discipline that aims to unravel the intricate workings of the human brain and mind.Brain tumors, ranging from non-cancerous to malignant forms poses a significant diagnostic challenge due to the presence of more than 100 distinct types. Effective treatment hinges on the precise detection and segmentation of these tumors at an early stage. To address this, we introduce a cutting-edge deep learning approach employing a Binary Convolutional Neural Network (BCNN).